Deep and Proximate Determinants of the World Income Distribution. (27th August 2019) - Fiaschi, Davide; Lavezzi, Andrea Mario; Parenti, Angela
Abstract : This paper studies the deep and proximate determinants of the evolution of the cross‐country distribution of GDP per worker in the period 1960–2008 by a novel method based on an information criterion. We find that countries of our sample follow three distinctive growth regimes identified by two deep determinants, namely life expectancy at birth in 1960 and the share of Catholics in 1965, and that each regime is characterized by non‐linearities. Growth regimes appear to be the main cause of the increased inequality and polarization, while technological catch‐up, proxied by the initial level of GDP per worker, acts in the opposite direction. Finally, human capital marginally reduces polarization, while investment rates and employment growth have no distributional effect.